Analyzing the Effectiveness of Wi-Fi 6E in Mitigating Interference in Industrial Environment - Roziyani Rawi; Mohd Isa, Mohd Rizal; Mohd Nazri Ismail; Muhamad Za’im Afham Zainal Abidin; Aznida Abu Bakar Sajak; Noormadinah Allias; Nur Farahwahida Ab Aziz; Nur Diyana Kamarudin (International Journal of Integrated Engineering, 2024)
Wi-Fi is a widely used wireless technology that is constantly evolving to meet demands for high throughput, real-time communication, dense networks, and resource efficiency. It provides broadband wireless connectivity between end users via unlicensed 2.4GHz and 5GHz frequency bands. Despite many benefits offered by the technology such as mobility, flexibility, and low cost, the limitation in propagating radio frequency (RF) signals over the existing frequency becomes a challenge in some environments, especially in a densely packed manufacturing environment. Thus, this study aims to investigate the effectiveness of the newly introduced Wi-Fi 6E which uses a 6GHz unlicensed frequency band in mitigating the effect of RF interference and obstructions in a densely packed manufacturing environment. This study focuses on evaluating the Wi-Fi performance of a selected printing manufacturing building under line-of-sight (LOS) and non-line-of-sight (NLOS) environments. The effect of obstacles, the source of interferences, and the distance toward the Wi-Fi signal strength and latency are measured using Acrylic W-Fi Analyzer, NetSpot Heatmapper and Ping tools. The results indicate that at the same distance in both NLOS and LOS environments, the 6GHz frequency has the lowest latency compared to the 2.4GHz and 5GHz frequencies. Additionally, the signal strength received from the 6GHz access point (AP) is significantly high at shorter distances in high interference environments but decreases as the distance between the AP and the end devices increases. The findings of this research can significantly enhance existing knowledge by offering valuable insights into the potential application of Wi-Fi 6E for Wi-Fi deployment in manufacturing environments.